Creating an Inclusive Educational Environment for Children with Special Educational Needs - Nilufar Abidova (Zien Journals, 2023)
The article discusses the issue of the conditions for providing accessible education for children with special educational needs, the development of special education in Uzbekistan and its situation at this stage of development
Keywords: children with special educational needs; inclusive education; special education